1993
DOI: 10.1007/bf00050754
|View full text |Cite
|
Sign up to set email alerts
|

The phosphorus cycle in coastal marine sediments

Abstract: 320sediment cores collected at three soft bottom stations; two brackish-marine and one freshwater. One of the marine stations was reduced and azoic, whereas the freshwater and the other marine station had well oxygenated conditions in the bottom waters. Positive redox-turnovers, including anaerobic incubation followed by reaeration, were generated in the cores and the supernatant water.In cores from the oxygenated freshwater and marine stations, dissolved phosphate and ferrous ions were released from the sedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 9 publications
8
91
0
1
Order By: Relevance
“…These findings are reinforced by other studies, in which HPO 4 2-in porewater were positively correlated with bottom water temperature (Jensen et al 1995;Lillebø et al 2004), and negatively correlated with dissolved oxygen (Jensen et al 1995). During the period of lower temperatures, the oxygen availability increases in porewater due to an increase of its solubility (Ohtake et al 1984;Moutin 1992), which turns the iron and sulphur cycles very reactive (Sundby et al 1992;Bally et al 2004;Caetano et al 2003). The low levels of HPO 4 2-found in porewater of muddy sediments (<10 lM) may be partially explained by P-sorption onto iron oxides formed under oxic conditions (Sundby et al 1992;De Jonge et al 1993;Van Raaphorst and Kloosterhuis 1994;Slomp et al 1998;Perkins and Underwood 2001), since there is a large iron availability in the intertidal muddy sediments of this lagoon (Caetano et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are reinforced by other studies, in which HPO 4 2-in porewater were positively correlated with bottom water temperature (Jensen et al 1995;Lillebø et al 2004), and negatively correlated with dissolved oxygen (Jensen et al 1995). During the period of lower temperatures, the oxygen availability increases in porewater due to an increase of its solubility (Ohtake et al 1984;Moutin 1992), which turns the iron and sulphur cycles very reactive (Sundby et al 1992;Bally et al 2004;Caetano et al 2003). The low levels of HPO 4 2-found in porewater of muddy sediments (<10 lM) may be partially explained by P-sorption onto iron oxides formed under oxic conditions (Sundby et al 1992;De Jonge et al 1993;Van Raaphorst and Kloosterhuis 1994;Slomp et al 1998;Perkins and Underwood 2001), since there is a large iron availability in the intertidal muddy sediments of this lagoon (Caetano et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This, in combination with N lost through denitrification, is a major reason that primary production in Narragansett Bay is predominantly N limited (Nixon et al 1980;Howarth 1988). On the other hand, the P released from sediments in Chesapeake Bay is less than the amount released during decomposition (Boynton and Kemp 1985), and there is evidence of P adsorption and storage in surface sediments in several other estuaries (van Raaphorst et al 1988;Koop et al 1990;Sundby et al 1992). Many of the differences in P uptake and release from sediments in both estuaries and lakes may be explained in part by the extent of eutrophication in those systems.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Recent experiments in the North Sea revealed that anammox rates did not change during exposure to short-term hypoxia (Neubacher et al 2011), whereas prolonged hypoxia significantly stimulated anammox activity (Neubacher et al 2013). Under anoxic conditions, inorganic P is efficiently regenerated, in particular in iron-rich sediments (Sundby et al 1992). It is not clear how bottom water oxygen concentrations and organic matter content and composition affect benthic microbial N transformation pathways and alter the stoichiometry of regenerated N and P in eutrophic seas.…”
Section: Introductionmentioning
confidence: 99%